Prediction of hydraulic fracturing parameters in terrigenous reservoirs at Rakytnyanske gas field with regard to geomechanical properties of rocks - Rubel, Victoriia; Pshyk, Vadym (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of fracture formation in the terrigenous reservoirs at the Rakytnyanske gas field, located in Ukraine in the Kharkiv oblast. The formation of fractures in the productive horizon has been investigated by designing hydraulic fracturing (HF), which is used to stimulate fluid inflow under the conditions of well #4. This method involves the use of innovative hydraulic fracturing fluids, which allows for the optimal geometry of the fractured formation, its sufficient conductivity and, ultimately, an increase in the well productivity. Hydraulic fracturing is one of the most effective methods for improving well production, especially in low-permeability and complex formations. This technology is widely used in the oil and gas industry to develop both conventional and unconventional reservoirs. By creating a system of fractures in the reservoir, hydraulic fracturing makes it possible: – to improve the permeability in the formation zone around the reservoir; – to increase the area of fluid filtration through the formation to the well; – to change the direction of fluid flow in the formation. The basic hydraulic fracturing operation performed has resulted in a fracture with a half-length of 136.9 m, a total fracture height of 36.5 m, and a width of 0.0 mm to 3.7 mm with an average value of 1.5 mm. Thus, the crack was longer than designed under reduced profile geometry parameters. The crack formed at a high average wellhead pressure of 560 kgf/cm2. During the basic hydraulic fracturing process, 120 m3 of fluid and 23.9 tons of propane were injected, thereby achieving an average concentration of 2.57 kg/m2, which created conditions for the preservation of the main fracture and channels, their consolidation, as well as enabled good permeability. The simulation results obtained using FracCADE software were successfully applied to the Rakytnyanske gas field development project in the Kharkiv oblast. By optimizing the hydraulic fracturing process in complex geological structures, it was possible to increase well production rates by more than 35 times and reduce costs